2022
DOI: 10.21203/rs.3.rs-2253124/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

VOCs species controlling O3 formation in ambient air and their sources in Kaifeng, China

Abstract: The concentration of ozone has been in a rising crescendo in the last decade while the fine particles (PM2.5) is gradually decreasing but still at a high level in central China. Volatile organic compounds (VOCs) are the vital precursors of ozone and PM2.5. A total of 101 VOC species were measured in four seasons at five sites from 2019 to 2021 in Kaifeng. VOC sources and geographic origin of sources were identified by the positive matrix factorization (PMF) model and the HYbrid Single-Particle Lagrangian Integ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…Additionally, ozone (O 3 ) pollution is becoming increasingly prevalent [ 2 ]. Volatile organic compounds (VOCs) are widely recognized as major precursors of O 3 and PM 2.5 , which have a serious impact on environmental quality and human health [ 3 ]. Toluene (T), ethyl acetate (EA), and n -hexane (H) are among the most frequently used as industrial solvents, and are major pollutants found in the exhaust air of printing facilities [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, ozone (O 3 ) pollution is becoming increasingly prevalent [ 2 ]. Volatile organic compounds (VOCs) are widely recognized as major precursors of O 3 and PM 2.5 , which have a serious impact on environmental quality and human health [ 3 ]. Toluene (T), ethyl acetate (EA), and n -hexane (H) are among the most frequently used as industrial solvents, and are major pollutants found in the exhaust air of printing facilities [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%